Biaxially oriented polyester film
Patent Information
- Application Number
- JP2026054323
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-31
- Filing Date
- 2026-03-27
- Publication Date
- 2026-10-14
AI Technical Summary
【0007】 本発明によれば、動摩擦係数に優れる、新たなマット調の外観を示すポリエステルフィルムを提供することができる。本発明のポリエステルフィルムは、耐ブロッキング性にも優れているため、キャリアフィルムといった工程フィルムとして好適に用いることができる。
Smart Images

Figure 2026167598000001 
Figure 2026167598000002 
Figure 2026167598000003
Abstract
Description
Technical Field
[0001] The present invention relates to a polyester film having a matte appearance.
Background Art
[0002] Polyester films are widely used in industrial and technical fields due to their excellent mechanical properties, heat resistance, and chemical resistance. Among them, polyester films are suitably used as process films such as carrier films.
[0003] For use as a process film, various properties including blocking resistance and releasability are required. To improve blocking resistance and releasability, methods for matting the surface of polyester films are known. For example, methods of incorporating particles into the film as disclosed in Patent Documents 1 and 2 are known.
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Patent Document 2
Summary of the Invention
Problems to be Solved by the Invention
[0005] The present invention aims to provide a polyester film that exhibits a matte appearance different from the polyester films described in the above patent documents, shows a favorable dynamic friction coefficient, and has excellent blocking resistance.
Means for Solving the Problems
[0006] The gist of the present invention is as follows. (1) A biaxially oriented polyester film characterized in that at least one surface is composed of a polyester film layer A containing particles, the arithmetic mean height Sa of the surface of the polyester film layer A is 0.04 μm or more, and the haze is 10% or more. (2) The biaxially oriented polyester film according to (1), characterized in that the gloss (20 degrees) of the surface of the polyester film layer A is 10 to 60%. (3) The polyester film layer A is a biaxially oriented polyester film according to (1) or (2) and contains particles with an average particle diameter of 2.0 to 5.0 μm. (4) A biaxially oriented polyester film according to any of (1) to (3) above, wherein the biaxially oriented polyester film is a multilayer film, and a polyester film layer B different from polyester film layer A is laminated therein. [Effects of the Invention]
[0007] According to the present invention, it is possible to provide a polyester film exhibiting a new matte appearance with excellent dynamic friction coefficient. Since the polyester film of the present invention also has excellent blocking resistance, it can be suitably used as a process film, such as a carrier film. [Modes for carrying out the invention]
[0008] The polyester film of the present invention is composed of a polyester film layer A on which at least one surface contains particles.
[0009] The polyester film of the present invention may be a single layer or a multi-layer film formed by laminating two or more layers. The layer structure of the multilayer film is not particularly limited, but it is preferable that polyester film layer A is at least one of the outermost layers. Examples include two types of three layers (A / B / A), three types of three layers (A / B / C), and two types of two layers (A / B) obtained by melt-extruding different resins. The polyester film of the present invention may be composed entirely of polyester film layer A, but layers other than polyester film layer A may be laminated to prevent breakage during the film stretching process, improve film strength, enhance transparency and other physical properties, and improve productivity (hereinafter, polyester film layers other than polyester film layer A may be referred to as polyester film layer B and polyester film layer C). In the case of a multilayer film, pre-consumer materials such as self-recycled film raw materials or post-consumer materials such as recycled raw materials recovered from collected PET bottles may be used for layers other than the surface layer. Even if the above raw materials are used for layers other than the surface layer, it does not affect the transportability of the surface layer, so it is preferable from the viewpoint of cost reduction and reduction of environmental impact.
[0010] The polyester constituting the polyester film of the present invention is not particularly limited, and examples include polyethylene terephthalate, polybutylene terephthalate, and polytrimethylene terephthalate. Among these, polyethylene terephthalate can be suitably used because it has an excellent balance of heat resistance and mechanical properties, as well as excellent stretchability.
[0011] Other components may be copolymerized with the aforementioned polyester. Examples of other copolymerization components include isophthalic acid, phthalic acid, 2,6-naphthalenedicarboxylic acid, 5-sodium sulfisoisophthalic acid, oxalic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, dodecanoic acid, dimer acid, maleic anhydride, maleic acid, fumaric acid, itaconic acid, citraconic acid, and mesaconic acid, as dicarboxylic acid components. Other glycol components that can be used as copolymers include diethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, 1,6-hexanediol, cyclohexanedimethanol, triethylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, and ethylene oxide adducts of bisphenol A and bisphenol S.
[0012] In the present invention, the polyester constituting the polyester film layer A can be produced by conventionally known methods. For example, polyethylene terephthalate can be produced by esterifying terephthalic acid with ethylene glycol or by transesterifying dimethyl terephthalate with ethylene glycol, and then polycondensing the reaction products. In the polymerization described above, known catalysts can be used, and as transesterification catalysts in melt polymerization, manganese, calcium, magnesium, and titanium oxides, chlorides, carbonates, and carboxylates are preferred, with acetates being particularly preferred, namely manganese acetate, calcium acetate, magnesium acetate, and titanium acetate. Furthermore, examples of polymerization catalysts include antimony compounds, titanium compounds, and germanium compounds. Preferred antimony compounds include antimony trioxide, antimony pentoxide, and antimony acetate. Preferred titanium compounds include organotitanium compounds, such as those described in Japanese Patent Publication No. 5-298670. More specifically, examples include titanium alcoholates and organic salts, reaction products of tetraalkyl titanates with aromatic polycarboxylic acids or their anhydrides, and preferred specific examples include titanium tetrabutoxide, titanium isopropoxide, titanium oxalate, titanium acetate, titanium benzoate, titanium trimellitate, and reaction products of tetrabutyl titanate with trimellitic anhydride. Examples of germanium compounds include germanium dioxide and germanium tetrachloride, with germanium dioxide being preferred due to the excellent hue and transparency of the resulting polyethylene terephthalate. The polyester obtained by the above method (melt polymerization) can be further polymerized to a higher degree by solid-phase polymerization, and the precipitation of oligomers can be suppressed.
[0013] The intrinsic viscosity of the polyester resin constituting the polyester film layer A is preferably 0.50 to 0.90 dl / g, more preferably 0.55 to 0.80 dl / g, from the viewpoints of improving the mechanical strength of the film and the workability of sheet extrusion molding. When the intrinsic viscosity satisfies the above range, breakage during film formation can be suppressed and stable production can be achieved. Furthermore, the obtained film also has high strength, and thickness control becomes possible.
[0014] The melting point of the polyester resin constituting the polyester film layer A is preferably 220 to 280°C, more preferably 240 to 270°C.
[0015] The glass transition temperature of the polyester resin constituting the polyester film layer A is preferably 50 to 90°C, more preferably 70 to 85°C.
[0016] The A layer constituting the outermost surface of the polyester film of the present invention is required to have a surface roughness parameter Sa (arithmetic mean height) of 0.04 μm or more, preferably 0.06 μm or more, and more preferably 0.08 μm or more, from the viewpoint of transportability. If it is less than 0.04 μm, the slip property is poor, so scratches are likely to occur due to friction with rolls during transport, and the operability tends to deteriorate.
[0017] The haze of the polyester film of the present invention is required to be 10% or more, preferably 12% or more, and more preferably 15% or more, from the viewpoints of improving visibility and achieving a matte appearance. Although there is no particular upper limit set for the haze of the polyester film layer A, it is preferably 95% or less, for example.
[0018] In addition to improving blocking resistance and releasability, the polyester film of the present invention preferably has a glossiness (20°) of 10 to 60% on the surface of the polyester film layer A, more preferably 20 to 50%, and even more preferably 25 to 50%, from the viewpoints of improving operability, enhancing mechanical strength, and suppressing mold contamination. By setting the glossiness (20°) within the above range, the trouble of entrapping air during winding is reduced, and when used as a transfer film, a matte appearance can be transferred to the counterpart material.
[0019] Examples of methods for adjusting the glossiness of the film include the sand mat method and the particle kneading method described in JP 2012-194514 A. Since the polyester film obtained by the sand mat method may contaminate molds and the like with residues or scraped resin debris, the particle kneading method is preferred for suitable use as a process film.
[0020] In the present invention, examples of the particles contained in the polyester film layer A include inorganic particles and organic particles. As the inorganic particles, known ones are used, and examples thereof include silicon oxide (silica), titanium oxide, calcium carbonate, barium sulfate, aluminum oxide, zeolite, kaolin, clay, talc, mica and the like. Silicon oxide is preferred due to its narrow particle size distribution and low cost. As the organic particles, known ones are used, and examples thereof include particles of melamine resin, polystyrene, organic silicone resin, acrylic-styrene copolymer and the like. The component of the organic particles may be a single component or two or more components, and examples of using two or more components simultaneously include particles of crosslinked acrylic, crosslinked polystyrene, crosslinked melamine and the like.
[0021] The average particle diameter of the particles contained in the polyester film layer A is preferably 2.0 to 5.0 μm from the viewpoints of setting the arithmetic mean height Sa within a predetermined range, suppressing particle shedding from the polyester film layer A, and suppressing film cutting.
[0022] The particle content in polyester film layer A is not particularly limited as long as the arithmetic mean height Sa of the surface of polyester film layer A is 0.04 μm or more and the haze of the polyester film is 10% or more. Specifically, it is preferably 0.01 to 10.0 mass%, more preferably 0.1 to 5.0 mass%, and even more preferably 0.3 to 3.0 mass%. If the particle content in polyester film layer A is less than 0.01% by mass, the number of protrusions on the film surface will be reduced, and the anti-blocking function may not be able to be performed. On the other hand, if the particle content exceeds 10.0% by mass, it becomes difficult to retain the particles within polyester film layer A, and the particles may fall out or the film may break.
[0023] The thickness of the polyester film layer A is preferably 0.5 μm or more, preferably 0.5 to 20 μm, and more preferably 1 to 10 μm. If the thickness of polyester film layer A is less than 0.5 μm, it becomes difficult to retain the contained particles within polyester film layer A, and the particles may fall out.
[0024] As described above, the polyester film of the present invention may consist entirely of polyester film layer A, but layers other than polyester film layer A may be laminated from the viewpoint of preventing tearing during the film stretching process, film strength, productivity, and other physical properties. The resins constituting the layers other than polyester film layer A (for example, polyester film layer B and polyester film layer C) include ordinary polyester. Since polyester film layer B, which is made of this polyester, is an inner layer of the film, a polyester resin with reduced particle content may be used, and recycled polyester resin can be used. By using such polyester resin in the inner layer of the multilayer, it is possible to improve productivity and obtain a film with reduced environmental impact. Furthermore, for applications where visibility is required, it is preferable to include titanium dioxide as inorganic particles. By adding particles with a different particle size than those contained in layer A to polyester film layer C, or by changing the amount of particles added, the blocking prevention effect of the film can be improved.
[0025] The thickness of the polyester film, which consists of layers other than polyester film layer A, is not particularly limited, but is preferably 5 to 500 μm from the viewpoint of improving film strength and productivity.
[0026] The overall thickness of the polyester film of the present invention is preferably 5 to 1000 μm. More preferably 5 to 100 μm from the viewpoint of improving film productivity.
[0027] Next, an example of a method for producing the polyester film of the present invention will be described. The polyester film of the present invention is preferably stretched in at least one axis direction, and more preferably stretched in two axes, from the viewpoint of ease of adjusting surface roughness and gloss. Since the particles in the polyester film layer A containing particles only become raised on the surface when stretched, resulting in a film with a matte appearance, the gloss and surface roughness can be adjusted by the stretching ratio.
[0028] If the polyester film of the present invention is a laminated film in which a polyester film layer A and other layers are laminated, it is preferable to extrude all layers by a co-extrusion method in which they are melt-extruded from a die, and then form the film by stretching in two axes and heat-fixing. In detail, the resin constituting polyester film layer A and the resin constituting the other layers (e.g., layer B and layer C) are each supplied to separate melt extrusion devices. They are melted at a temperature between their respective melting points and (melting point + 40°C), and then co-extruded into a sheet form through filters using feed block type or multi-manifold type T-dies. In other words, multiple melt extrusion devices can be used depending on the type of resin used in the polyester film layer. The co-extruded laminated sheet is brought into close contact with a cooling drum heated to 30°C or below using known methods such as electrostatic casting or air knife method, and rapidly cooled and solidified to a temperature below the glass transition temperature to obtain an unstretched sheet of the desired thickness.
[0029] Next, the obtained unstretched sheet is biaxially stretched and heat-set to obtain a polyester film with a matte finish, excellent gloss, mechanical properties, and dimensional stability. Examples of biaxial stretching methods include simultaneous biaxial stretching, in which the film is stretched simultaneously in the longitudinal and transverse directions using a tenter-type simultaneous biaxial stretching machine, and sequential biaxial stretching, in which the film is stretched longitudinally using a roll-type stretching machine and then transversely using a tenter-type transverse stretching machine. The stretching ratio is the area ratio of the polyester film, preferably 3 times or more, more preferably 4 to 20 times, and even more preferably 6 to 15 times. If the stretching ratio exceeds 20 times, the voids become too large, which can increase the frequency of film breakage. The stretching temperature is preferably in the range of (glass transition temperature + 5°C) to (glass transition temperature + 60°C) of the polyester, and more preferably in the range of (glass transition temperature + 15°C) to (glass transition temperature + 55°C). Stretching near the glass transition temperature increases the load on the stretching equipment, tends to create larger voids, and may increase the frequency of film breakage.
[0030] After stretching, the film is heat-set in a tenter at a temperature of 150°C (5°C below the melting point of polyester) for several seconds, with a relaxation rate of 0-10% in both the longitudinal and transverse directions. It is then cooled to room temperature and wound up at a speed of 20-250 m / min. The heat-setting treatment after stretching described above is a process to reduce the thermal shrinkage rate of the polyester film. Examples of heat-setting treatment methods include blowing hot air, irradiating with infrared rays, and irradiating with microwaves. Among these, blowing hot air is preferred because it can heat the film uniformly and accurately.
[0031] The polyester film of the present invention has good transportability, allows for easy removal of oligomers precipitated on the film surface by heat treatment, and provides a film that is easy to peel off even after heat processing. Therefore, it can be suitably used as a release film for resin molding processes that involve a heat treatment process, as well as as a carrier film for semiconductors and as a masking film for automobiles.
[0032] A coating layer may be provided by applying a coating liquid to the polyester film layer A or other layer that constitutes the outermost layer of the polyester film of the present invention, and then heating and drying it.
[0033] The polyester film to which the coating solution is applied may be an unstretched film, a uniaxially oriented film, or a biaxially oriented film. Since the drying and curing reactions of the coating solution can proceed simultaneously with the stretching and heat-fixing treatments, it is preferable to coat an unstretched film when manufacturing polyester films by uniaxial stretching or simultaneous biaxial stretching, and it is preferable to coat a uniaxially oriented film when manufacturing by sequential biaxial stretching. If necessary, it is preferable to provide a pre-drying step before stretching after coating.
[0034] When the polyester film of the present invention is used for release purposes, for example, in the medical field it can be used as a protective film for medical tapes and poultices, and in the industrial field it can be used as a carrier film that can be used in semiconductor pressing processes. It can also be used as a process film for manufacturing printed circuit boards, flexible printed circuit boards, multilayer printed circuit boards, etc., as well as a protective film for adhesive materials, liquid crystal display components, glass, solar panels, etc., and as a molding film for sheet-like structures such as ion exchange membranes and ceramic green sheets. Furthermore, the polyester film obtained by the manufacturing method of the present invention can be used in applications other than release purposes by forming a resin layer having a specific function on the base layer. For example, it can be used in a variety of applications such as antistatic films, easy-adhesion films, barrier films, water-repellent films, hydrophilic films, weather-resistant films, antifouling films, solvent-resistant films, self-healing films, hard coat films, and optical films. [Examples]
[0035] The present invention will be specifically described below with reference to examples, but the present invention is not limited thereto.
[0036] <Polyester resin P-1: Silica-containing polyester resin> A polyethylene terephthalate resin containing 1.7% by mass of amorphous silica particles SYLYSIA310P (average particle size 2.7 μm) from Fuji Silysia Chemical Co., Ltd. (polymerization catalyst: antimony trioxide, resin viscosity: 0.62 dl / g, glass transition temperature: 78°C, melting point: 255°C). The average particle size of the silica particles in the resin is 2.9 μm. <Polyester resin P-2: Silica-containing polyester resin> A polyethylene terephthalate resin containing 1.4% by mass of amorphous silica particles SYLYSIA310P (average particle size 2.7 μm) from Fuji Silysia Chemical Co., Ltd. (polymerization catalyst: antimony trioxide, resin viscosity: 0.62 dl / g, glass transition temperature: 78°C, melting point: 255°C). The average particle size of the silica particles in the resin is 3.0 μm. <Polyester resin P-3: Silica-containing polyester resin> A polyethylene terephthalate resin containing 1.7% by mass of amorphous silica particles SYLYSIA310P (average particle size 2.7 μm) from Fuji Silysia Chemical Co., Ltd. (polymerization catalyst: antimony trioxide, resin viscosity: 0.62 dl / g, glass transition temperature: 78°C, melting point: 255°C). The average particle size of the silica particles in the resin is 3.5 μm. <Polyester resin P-4: Silica-free polyester resin> Silica-free polyethylene terephthalate resin (resin viscosity: 0.64 dl / g, glass transition temperature: 78°C, melting point: 252°C) <Polyester resin P-5: Silica-free polyester resin> Silica-free polyethylene terephthalate resin (UT-CBR, manufactured by Nippon Ester Co., Ltd.; polymerization catalyst: antimony trioxide; resin viscosity: 0.62 dl / g; glass transition temperature: 78°C; melting point: 252°C) <Polyester resin P-6: Silica-free polyester resin> Silica-free polyethylene terephthalate resin (resin viscosity: 0.65 dl / g, glass transition temperature: 78°C, melting point: 263°C) <Polyester resin P-7: Silica-free polyester resin> Silica-free polyethylene terephthalate resin (resin viscosity: 0.69 dl / g, glass transition temperature: 78°C, melting point: 252°C)
[0037] 1.Measurement method (1) Viscosity (intrinsic viscosity) of polyester resin The viscosity of the polyester resin was measured using a conventional method under conditions of a sample concentration of 0.5% by mass and a temperature of 20°C, with an equal mass mixture of phenol and tetrachloroethane as the solvent.
[0038] (2) Glass transition temperature and melting point of polyester resin In accordance with Japanese Industrial Standard JIS K7121, a PerkinElmer differential scanning calorimeter (input-compensated DSC8000) was used to measure a 10 mg sample of polyester resin. The measurement conditions involved heating from 25°C to 300°C at a heating rate of 20°C / min. The glass transition point and melting point were determined from the resulting chart.
[0039] (3) Average particle diameter of the particles Using an oblique cutting device (DN-20S, manufactured by Daipla Wintes Co., Ltd.), only polyester film layer A was cut away. The polyester film layer A was then dissolved in a phenol / tetrachloroethane mixed solvent of 50 / 50 (mass ratio) to prepare a sample with a diffraction / scattering light intensity of 40-60%. The sample was then measured using a laser diffraction / scattering particle size analyzer (SALD-2300, manufactured by Shimadzu Corporation), and the volume-average particle size was taken as the average particle size of the particles.
[0040] (4) Glossiness (20 degrees) In accordance with the method specified in JIS-Z-8741, the 20-degree specular gloss was measured on the surface of polyester film layer A and the opposite surface of surface A of the polyester film using a gloss meter (VG7000 manufactured by Nippon Denshoku).
[0041] (5) Total light transmittance and haze of polyester film Based on JIS-K7136:2000, the diffuse transmittance and total light transmittance of the polyester film were measured using a haze meter NDH4000 (manufactured by Nippon Denshoku), and the haze was calculated.
[0042] (6) Surface roughness parameters Sa (arithmetic mean height), Sz (maximum height) Using a Hitachi High-Tech VS1800 nano 3D optical interferometry system, surface roughness parameters Sa (arithmetic mean height, μm) and Sz (maximum height, μm) were measured at 10 locations on the surface of polyester film layer A and the opposite surface of A, and the average values of each were used as the measurement results.
[0043] (7) Other surface roughness parameters For the polyester films obtained in Examples 1, 6, 8, 11, 13, 18, 20, 27, 29, and 30, a Hitachi High-Tech Nano 3D Optical Interferometry System VS1800 was used to measure the surface of polyester film layer A and the layer opposite it, using three-point surface roughness parameters: Sk (level difference of the core, μm), Spk (height of the protruding peaks, μm), Svk (height of the protruding valleys, μm), Smr1 (area ratio of the protruding peaks, %), and Smr2 (area ratio of the protruding valleys, %). Sxp (pole height, μm), Sq (root mean square height, μm), Ssk (skewness (symmetry of height distribution)), Sku (curtsis (sharpness of height distribution)), Sp (maximum peak height, μm), Sv (maximum valley height, μm), Sdq (root mean square slope), Sdr (interface area ratio, %), Sal (minimum autocorrelation length, μm), Str (aspect ratio of surface texture), Std (direction of surface texture, degrees), Vvv (volume of space in protruding valleys, ml / m³) 2 ), Vvc (volume of the space in the core, ml / m³) 2 ), Vmp (volume of the protruding peak, ml / m³) 2 ), Vmc (volume of the core, ml / m³) 2 ) was measured at 10 locations, and the average value of each measurement was used as the measurement result.
[0044] (8) Coefficient of kinetic friction In accordance with JIS-K7125, the coefficient of dynamic friction of surface A of the polyester film layer was measured using a TR-2 friction measuring instrument manufactured by Toyo Seiki Seisakusho Co., Ltd. A smaller coefficient of dynamic friction indicates better slip properties.
[0045] (9) Evaluation of blocking resistance Two A4-sized pieces of the polyester film obtained in the example were cut out, and the opposite sides of polyester resin layer A and polyester resin layer A were brought into contact. A load of 1 kg was applied to a 10 cm square area, and the film was left standing for 24 hours at 23°C and 50% RH. After that, the blocking resistance was evaluated based on the conditions when the stacked films were peeled apart, according to the following criteria. ○: The film can be peeled off without resistance. ×: There is significant resistance when peeling off the film, making it difficult to remove.
[0046] (10) Dry heat shrinkage rate (%) For the polyester films obtained in Examples 1, 6, 8, 11, 13, 18, 20, 27, 29, and 30, the central portion in the TD direction was cut out in the MD direction and the TD direction to a width of 10 mm and a length of 150 mm, a gauge mark of 100 mm in length was marked, and the film was treated in hot air at 160 °C for 15 minutes. The distance between the gauge marks (mm) after treatment was read and calculated using the following formula. Dry heat shrinkage rate (%) = (Gauge length before treatment - Gauge length after treatment) / Gauge length before treatment × 100
[0047] Example 1 A raw material blend consisting of 39% by mass of crystallized and dried polyester resin P-1 and 61% by mass of crystallized and dried polyester resin P-4 was fed into extruder A. A raw material blend consisting of 23.8% by mass of crystallized and dried polyester resin P-1 and 76.2% by mass of crystallized and dried polyester resin P-4 was fed into extruder B. A raw material blend consisting of 39% by mass of crystallized and dried polyester resin P-1 and 61% by mass of crystallized and dried polyester resin P-4 was fed into extruder C. After melting at 280°C in each extruder, the material was extruded from the T-die so that the thickness ratio of layers A / B / C was (1.14 / 9.72 / 1.14). The material was then rapidly cooled by adhering it to a cooling drum with a surface temperature controlled to 20°C using an electrostatic application method to obtain an unstretched film with a thickness of 210 μm. This unstretched film was stretched 3.4 times in the longitudinal direction under conditions of 85°C using a roll-type longitudinal stretcher. Subsequently, the ends of the film were continuously gripped by clips on a flat stretcher, and stretched 5.0 times transversely under conditions of 120°C. After that, a heat-setting treatment was performed at 230°C for 3 seconds with a transverse relaxation rate of 2.5%. The film was then wound into a roll to obtain a polyester film with a thickness of 12 μm (A layer / B layer / C layer = 1.14 μm / 9.72 μm / 1.14 μm).
[0048] Example 2 A raw material blend consisting of 23.4% by mass of crystallized and dried polyester resin P-1 and 76.6% by mass of crystallized and dried polyester resin P-5 was fed into extruder A. A raw material blend consisting of 42.7% by mass of crystallized and dried polyester resin P-1 and 52.3% by mass of crystallized and dried polyester resin P-5 was fed into extruder B. After melting at 280°C in each extruder, the two types and three layers were combined in a feed block and extruded from a T-die so that the thickness ratio of layer A / layer B / layer A was (1 / 10 / 1). An unstretched film was then obtained in the same manner as in Example 1. Subsequently, longitudinal stretching, transverse stretching, and heat setting treatment were performed to obtain a polyester film with a thickness of 12 μm (layer A / layer B / layer A = 1 μm / 10 μm / 1 μm).
[0049] Examples 3 and 4 As shown in Table 1, a polyester film with a thickness of 12 μm was obtained in the same manner as in Example 1, except that the type and content of polyester resin in each layer were changed.
[0050] Examples 5-7 As shown in Table 1, a polyester film with a thickness of 12 μm was obtained in the same manner as in Example 2, except that the type and content of polyester resin in each layer were changed.
[0051] Example 8 A polyester film with a thickness of 25 μm, corresponding to the thickness of each layer shown in Table 1, was obtained using the same method as in Example 1, except that the thickness of the unstretched film was changed to 430 μm.
[0052] Example 9 A polyester film with a thickness of 25 μm, corresponding to the thickness of each layer shown in Table 1, was obtained using the same method as in Example 2, except that the thickness of the unstretched film was changed to 430 μm.
[0053] Examples 10 and 11 As shown in Table 1, a polyester film with a thickness of 25 μm was obtained in the same manner as in Example 8, except that the type and content of polyester resin in each layer were changed.
[0054] Examples 12-14 As shown in Table 1, a polyester film with a thickness of 25 μm was obtained in the same manner as in Example 9, except that the type and content of polyester resin in each layer were changed.
[0055] Example 15 A polyester film with a thickness of 38 μm, corresponding to the thickness of each layer shown in Table 1, was obtained using the same method as in Example 1, except that the thickness of the unstretched film was changed to 650 μm.
[0056] Example 16 A polyester film with a thickness of 38 μm, corresponding to the thickness of each layer shown in Table 1, was obtained using the same method as in Example 2, except that the thickness of the unstretched film was changed to 650 μm.
[0057] Examples 17 and 18 As shown in Table 1, a polyester film with a thickness of 38 μm was obtained in the same manner as in Example 15, except that the type and content of polyester resin in each layer were changed.
[0058] Examples 19-21 As shown in Table 1, a polyester film with a thickness of 38 μm was obtained in the same manner as in Example 16, except that the type and content of polyester resin in each layer were changed.
[0059] Example 22 A polyester film with a thickness of 50 μm, corresponding to the thickness of each layer shown in Table 1, was obtained using the method described in Example 1, except that the thickness of the unstretched film was changed to 850 μm.
[0060] Example 23 A polyester film with a thickness of 50 μm, corresponding to the thickness of each layer shown in Table 1, was obtained using the method described in Example 2, except that the thickness of the unstretched film was changed to 850 μm.
[0061] Examples 24, 25 As shown in Table 1, a polyester film with a thickness of 50 μm was obtained in the same manner as in Example 22, except that the type and content of polyester resin in each layer were changed.
[0062] Examples 26-28 As shown in Table 1, a polyester film with a thickness of 50 μm was obtained in the same manner as in Example 23, except that the type and content of polyester resin in each layer were changed.
[0063] Example 29 Crystallized and dried polyester resin P-1 was fed 100% into extruder A, and crystallized and dried polyester resin P-4 was fed 100% into extruder B. After melting at 280°C in each extruder, the two types were combined in a 3-layer feed block and extruded from a T-die so that the A / B / A layers had a thickness ratio of (1 / 13 / 1). The film was then rapidly cooled by electrostatic application onto a cooling drum with a surface temperature controlled to 20°C to obtain an unstretched film with a thickness of 250 μm. This unstretched film was stretched 3.4 times in the longitudinal direction at 85°C using a roll-type longitudinal stretcher. Subsequently, the ends of the film were continuously gripped with clips on a flat-type stretcher and stretched 5.0 times in the transverse direction at 120°C. After that, a heat-setting treatment was performed at 230°C for 3 seconds with a transverse relaxation rate of 2.5%. The film was then wound into a roll to obtain a polyester film with a thickness of 15 μm.
[0064] Example 30 As shown in Table 1, a polyester film with a thickness of 15 μm was obtained in the same manner as in Example 29, except that the type of polyester resin in each layer was changed.
[0065] [Table 1]
[0066] The physical properties of each example are shown in Tables 2-4.
[0067] [Table 2]
[0068] [Table 3]
[0069] [Table 4]
[0070] The polyester films of Examples 1 to 30 had an arithmetic mean height Sa of 0.04 μm or more on the surface of the polyester film layer A, and a haze of 10% or more, resulting in polyester films with an excellent matte appearance, a good coefficient of dynamic friction, and excellent resistance to blocking.
Claims
1. A biaxially oriented polyester film characterized in that at least one surface is composed of a polyester film layer A containing particles, the arithmetic mean height Sa of the surface of the polyester film layer A is 0.04 μm or more, and the haze is 10% or more.
2. The biaxially oriented polyester film according to claim 1, characterized in that the gloss (20 degrees) of the surface of the polyester film layer A is 10 to 60%.
3. The biaxially oriented polyester film according to claim 1, wherein the polyester film layer A contains particles having an average particle diameter of 2.0 to 5.0 μm.
4. The biaxially oriented polyester film according to claim 1 is a multilayer film, wherein a polyester film layer B different from polyester film layer A is laminated to the biaxially oriented polyester film.
Citation Information
Patent Citations
Coextrusion laminated polyester film
JP2001322218A
Laminated mat-like polyester film
JP2006312263A